4-Octyl Itaconate and Dimethyl Fumarate Induce Secretion of the Anti-Inflammatory Protein Annexin A1 via NRF2 - O'Neill, Luke (My University, 2023)
Annexin A1 is a key anti-inflammatory effector protein that is involved in the anti-inflammatory effects of glucocorticoids. 4-Octyl itaconate (4-OI), a derivative of the endogenous metabolite itaconate, which is abundantly produced by LPS-activated macrophages, has recently been identified as a potent anti-inflammatory agent. The anti-inflammatory effects of 4-OI share a significant overlap with those of dimethyl fumarate (DMF), a derivate of another Krebs cycle metabolite fumarate, which is already in use clinically for the treatment of inflammatory diseases. In this study we show that both 4-OI and DMF induce secretion of the 33-kDa form of annexin A1 from murine bone marrow–derived macrophages, an effect that is much more pronounced in LPS-stimulated cells. We also show that this 4-OI– and DMF-driven annexin A1 secretion is NRF2-dependent and that other means of activating NRF2 give rise to the same response. Lastly, we demonstrate that the cholesterol transporter ABCA1, which has previously been implicated in annexin A1 secretion, is required for this process in macrophages. Our findings contribute to the growing body of knowledge on the anti-inflammatory effects of the Krebs cycle metabolite derivatives 4-OI and DMF
PUBLISHED
Keywords: Annexin A1; anti inflammatory; protein; Annexin A1; anti inflammatory; protein